دور التسويق الداخلي في أداء العاملين : دراسة ميدانية لعينة من العاملين في الوكالات السياحية في الجزائر - بلبخاري، سامي Belbekhari, Sami (جامعة السودان للعلوم والتكنولوجيا, 2018)
This study aimed at assessing the impact of the internal marketing dimensions, which include training, motivation, empowerment, service culture and internal communication on the employees’ performance. The study data was collected through distributing a questionnaire on a randomly simple sample of 131 employees in the Algerian Tourism Agencies. In order to test the study hypotheses, the Statistical Package for Social Science Program (SPSS) was used. The study results indicated the existence of a statistically significant effect of the motivation, empowerment, and internal communication on the employees’ performance at Tourism Agencies. The results also showed that internal communication policy was the strongest variable that influenced the employees’ performance. The study recommended that Algerian Tourism Agencies should pay more attention for internal marketing planning and programs; besides preserving these dimensions through adopting a more advanced marketing strategies due to their positive effect on employees’ performance.
تهدف هذه الدراسة لمعرفة أثر أبعاد التسويق الداخلي المتمثلة في: التدريب، التحفيز، التمكين، ثقافة الخدمة والاتصال الداخلي على أداء العاملين. وقد تم جمع البيانات من خلال استبانة الدراسة التي تم توزيعها على عينة احتمالية عشوائية بسيطة حجمها 131 عاملا في الوكالات السياحية في الجزائر، وقد تم استخدام برنامج الحزمة الإحصائية (SPSS) لاختبار فرضيات الدراسة. أظهرت نتائج الدراسة وجود أثر ذو دلالة إحصائية للتحفيز، التمكين والاتصال الداخلي على أداء العاملين في الوكالات السياحية، كما أشارت النتائج إلى أن أقوى المتغيرات الخاصة بالتسويق الداخلي تأثيرا على أداء العاملين تمثل في سياسة الاتصال الداخلي. وأوصت الدراسة بضرورة الاهتمام ببرامج وخطط التسويق الداخلي في الوكالات السياحية الجزائرية والمحافظة على تفعيل هذه الأبعاد باتباع استراتيجيات تسويق داخلي متطورة وسريعة الاستخدام لما لها من آثار إيجابية على أداء العاملين.
Keywords: الجزائر -- السياحة -- التسويق الداخلي -- إدارة الموارد البشرية